PROSES INOVASI PELAYANAN MELALUI PROGRAM SATU BERKAS MINIMAL EMPAT PRODUK (SABER MEMPRO) DI KABUPATEN PELALAWAN - ropizal, ropizal (Jurnal Ilmu Administrasi Negara, 2022)
The Saber Mempro program was formed due to the low coverage of Birth Certificates in Pelalawan Regency, which means that many Pelalawan people do not yet have a child's birth certificate, besides that, public awareness when dealing is still lacking due to the vulnerability of the village distance to Disdukcapil which uses fees, and government attention is still lack of socialization in providing effective services to the community. The purpose of this research is to find out. The purpose of this study was to determine the support and process of service innovation through the one file program of at least four products (Saber Mempro) in Pelalawan Regency. The research method used is qualitative research with a descriptive case study approach. The results of the study stated that the Mempro Saber Program at the Population and Civil Registration Office of Pelalawan Regency was carried out through an analysis of four stages in the innovation process: The stage of submitting an idea, having an idea first, the stage of evaluating ideas that will be followed up, the stage of developing ideas into reality, and the implementation stage according to Sherwood in Marzuki (2016:5).